Opinion 2451: Tupinambis indicus Daudin, 1802 (currently Varanus indicus; Reptilia, Squamata): specific name conserved - ICZN (Bulletin of Zoological Nomenclature, 2020)
The International Commission on Zoological Nomenclature has used its plenary power to conserve the accustomed usage of the specific names of Varanus indicus (Daudin, 1802) and Varanus chlorostigma Gray, 1831 by replacing the neotype specimen of Tupinambis indices Daudin, 1802 with a new neotype that belongs to the original taxonomic species involved.
Keywords: Nomenclature; taxonomy; Varanidae; Varanus chlorostigma; neotype; southwestern Pacific; Moluccas; Ambon; Ravak; New Guinea